Usefulness of a new sensorimotor control scale in patients with gonarthrosis and after total knee replacement - Słupik, Anna; Kowalski, Marcin; Białoszewski, Dariusz (European Journal of Clinical and Experimental Medicine, 2015)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. The importance of sensorimotor control assessment as a crucial factor determining functional recovery is being increasingly appreciated in clinical practice. The aim of this study was to assess the influence of damage associated with severe gonarthrosis on changes in proprioception and sensorimotor control of the knee, compare the results of a new sensorimotor control test developed by the authors with objective methods of proprioception assessment, and analyse the relation between the level of proprioception and sensorimotor system function and the measurements used in clinical practice. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. We studied a group of healthy persons (control group, n=74), patients with stage 4 knee osteoarthritis (group 1, n=67), and patients after total knee arthroplasty (group 2, n=62). The participants were assessed with a new sensorimotor control test (TKS) and a joint position sense test (JPS). Moreover, we analysed the patients’ HSS knee scores and Staffelstein scores. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. In the Control Group, mean TKS and JPS test scores were 4.9 pts and 3.9°, respectively, while the respective results in group 2 were 3.7 pts and 6.7° (p<0.005). In group 1, the TKS score was 3.2 pts and the JPS test result was 8.2° in the unaffected limb and 10.2° in the affected limb. The results of this group were significantly worse than the scores achieved in the control group and group 2 (p<0.005). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions. 1. The new knee sensorimotor control test developed by the present authors appears to provide an objective and comprehensive method to evaluate sensorimotor control of the knee in patients with gonarthrosis and after total knee replacement. 2. Further studies of the new test are advised, including an objective evaluation of the test utilising specialised measuring tools.